SEN virus--chystá se nové písmeno v abecedĕ virových hepatitid? - Husa, P; Chalupa, P; Husová, L (Vnitrni lekarstvi, 2002)
The SEN virus (SENV) is a small nonenveloped single-stranded DNA virus which is probably a circovirus. By phylogenetic analysis it is possible to differentiate genotypes SENV A-H. The pathway of transmission of infection is not known so far but the infection by this virus is frequent in recipients of blood transfusions and liver grafts and in intravenous drug addicts. This suggests possible parenteral transmission of infection. Other routes of transmission of the infection are also possible as the virus can be detected also in a significant proportion of young subjects without the risk of parenteral infection in the case-history. Whether SENV causes hepatitis has not been proved unequivocally so far. The prevalence of this infection does not differ significantly in patients with different liver diseases, acute or chronic viral or non-viral. SENV infection very probably does not influence the course of chronic hepatitis C.
Keywords: DNA Virus Infections; infekce DNA virem; DNA Viruses; Hepatitis, Viral, Human; virová hepatitida u lidí; DNA viry; Humans; lidé